Kinship and morphological similarity in the skeletal remains of individuals with known genealogical data (Bohemia, 19th to 20th centuries): A new methodological approach - Cvrček, Jan; Velemínský, Petr; Dupej, Ján; Vostrý, Luboš; Brůžek, Jaroslav (American journal of physical anthropology, 2018)
OBJECTIVES: This article proposes a new approach, called the "similarity coefficient" (SC) for verifying family relationships from skeletal remains using nonmetric traits. Based on this method and further analyses, the authors aim to show the degree of similarity between individuals with varying degrees of kinship, including inbred individuals. MATERIALS AND METHODS: Our sample includes the skeletal remains of 34 individuals with known genealogical data (four generations, 19th to 20th centuries). A total of 243 skeletal nonmetric traits were evaluated with respect to their anatomical characteristics. The SC was calculated by quantifying the agreement of trait occurrence between individuals. We also identified the traits that support the biological relationships of particular individuals by accounting for their population frequencies. RESULTS: There was a positive correlation between the morphological similarity of biologically related individuals and their biological distance. In some cases, we found greater degree of morphological similarity between first cousins than among other close relatives such as parents and children. At the same time, there was no statistically significant difference in the degree of similarity between inbred individuals and common relatives. Proven family relationships were best reflected by cranial traits, especially bone bridges associated with the courses of blood vessels and nerves. CONCLUSIONS: The use of skeletal nonmetric traits for the detection of relatives is possible. There is a relationship between biological distance and the degree of morphological similarity in related individuals. It also appears that inbreeding, despite previous assumptions, does not lead to a significant reduction in morphological variation.
Keywords: senioři; běloši; Family; senioři nad 80 let; History, 20th Century; dějiny 20. století; Česká republika; Genealogy and Heraldry; Middle Aged; mužské pohlaví; Inbreeding; Adult; mladý dospělý; inbreeding; Czech Republic; similarity coefficient; genealogical documented sample; Aged, 80 and over; Young Adult; antropologie fyzická; ženské pohlaví; dějiny 19. století; Anthropometry; Humans; genealogie a heraldika; Anthropology, Physical; lidé středního věku; kinship analysis; antropometrie; White People; morphological nonmetric traits; dospělí; rodina; Female; Aged; lidé; Male; History, 19th Century